(untitled) (International Journal of Engineering Materials and Manufacture, 2022)
Fire hazards caused by leakages in gas circulation lines are dangerous and pose a threat that results in a significant loss of wealth, lives, and the environment. By adopting significant precautions, the risks of fire hazards can be reduced effectively through the use of new technologies and preventive measurements of the system. In addition, the effects of fire hazards due to leakage in gas circulation lines in the buildings as well as in the other systems can be assessed to create the context of preventive measures for a fire protection system in a way to overcome the fire hazards in gas circulation lines. The paper aims to review the effects of fire hazards due to leakage in gas circulation lines in Bangladesh. It is noted that in Bangladesh during 2018-2019, the total gas distribution line in the Titas gas system was measured as 13,138 km where the pressure-reducing system or gas riser was found as 1.2 million and the number of customers was found as 2.866 million. In the system, the number of fire accidents that occurred was 208 in the circulation system. Because of connecting the illegal gas lines and poor maintenance of the system, Bangladesh faces significant fire hazards every year. To avoid this kind of problem, proper maintenance along with the varieties of new technologies incorporating sensors and microcontrollers can be utilized.